Análise estática e dinâmica de parques eólicos mistos compostos por aerogeradores de velocidade fixa e variável - SILVA, Helleson Jorthan Brito da (Universidade Federal do Pará, 2017)
The wind electric power generation systems are presented as an appropriate solution to meet the technical, economic, environmental, social and governmental requirements, therefore they have been largely used in several countries. Among the wind turbines technologies available, the speed-fixed with squirrel cage induction generator and variable-speed with doubly fed induction generator wind systems are the most popular. With increasing of the wind penetration levels in electrical grid and due the technologic drawbacks of the wind turbine with cage induction generator, a tend to replace this concept by wind turbine with doubly fed induction generator in the construction of new wind farms is seen. In the case of wind plant installed already, for economic reasons, the gradative modernization process is more convenient. Although both wind systems are well known, but about the combined operation of them is known a little. Thus, the present paper proposes a study to evaluate the impacts occurred by integration of a mixed wind farm in the electrical grid, with squirrel cage and doubly fed induction generators. Aspects related to transient stability under fault and short wind variations and voltage stability are analyzed. The interactions between the technologies are also object of study. Cases with different penetration levels of the wind systems are considered, representing the gradative replace of part of the old concept wind turbine by others of the concept more modern. The results obtained show that the characteristics of the doubly fed induction generator allied with the reduction of the power injection of the fixed-speed wind systems improve the wind farm behavior, suggesting that the combined operation of the wind turbines could be a more costeffective solution.